2013
DOI: 10.1002/humu.22309
|View full text |Cite
|
Sign up to set email alerts
|

Do Not Trust the Pedigree: Reduced and Sex-Dependent Penetrance at a Novel Mutation Hotspot inATL1Blurs Autosomal Dominant Inheritance of Spastic Paraplegia

Abstract: The hereditary spastic paraplegias (HSPs), a group of neurodegenerative movement disorders, are among the genetically most heterogeneous clinical conditions. Still, the more than 50 forms known so far apparently explain less than 80% of cases. The present study identified two large HSP families, which seemed to show an autosomal recessive and an X-linked inheritance pattern. A set of genetic analyses including exome sequencing revealed plausible mutations only when assuming incomplete/sex-dependent penetrance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Genetic studies show that B20% of cases reported with HSP are negative for mutations, and one potential explanation could be misinterpretation of the inheritance pattern when selecting candidate genes. 15 Our data demonstrate that ATL1 mutations can be taken into account in families with nondominant and even recessive inheritance of HSP. WES or complete gene panels in order to target all known SPG loci are thus preferred methods for improved genetic diagnosis in HSP that circumvents a selection bias based on inheritance patterns.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Genetic studies show that B20% of cases reported with HSP are negative for mutations, and one potential explanation could be misinterpretation of the inheritance pattern when selecting candidate genes. 15 Our data demonstrate that ATL1 mutations can be taken into account in families with nondominant and even recessive inheritance of HSP. WES or complete gene panels in order to target all known SPG loci are thus preferred methods for improved genetic diagnosis in HSP that circumvents a selection bias based on inheritance patterns.…”
Section: Discussionmentioning
confidence: 55%
“…15 The identification of ATL1 mutation in autosomal dominant HSN1D 21 further illustrates the clinical variability associated with ATL1 mutations. 22 The family investigated herein segregates 'pure' HSP compatible with both autosomal recessive and dominant inheritance and, strikingly, only males are affected.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that the amyotrophy of the extremities and retinitis pigmentosa were observed because ATL1 mutations could affect pathways other than the corticospinal tract, and the variability of clinical presentation with the same mutation may be due to genetic or environmental modulation. Moreover, incomplete penetrant was observed in a family with the c. 1246C>T, which was only reported in 3 European SPG3A cases with the mutations c.1243C>T and c.1244G>A [40,41]. Mutations in the C-terminal cytoplasmic part of the protein may be less deleterious, accounting for its incomplete penetrance, or varying penetrance may be due to environmental and/or genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Complicated SPG3A and the late-onset form are very rare (Sauter et al, 2004;Ivanova et al, 2007). AD inheritance is common, although autosomal recessive inheritance and sex-related penetrance have also been reported (Varga et al, 2013;Khan et al, 2014). In this study, family 4, which segregates the c.1204T>G ATL1 mutation, presents infancy-onset HSP, and the lower limb spasticity of female patients in this family is too severe to permit walking without double crutches.…”
Section: Discussionmentioning
confidence: 66%